2016
DOI: 10.1016/j.memsci.2016.04.034
|View full text |Cite
|
Sign up to set email alerts
|

Rapid annealing of sequentially plated Pd-Au composite membranes using high pressure hydrogen

Abstract: In this work, the time-consuming process of annealing Pd-Au alloy composite membranes, fabricated by sequential electroless plating, has been revisited. Composite Pd-Au/YSZ membranes approximately 5 µm thick with compositions ranging from 8 wt% to 10 wt% Au were fabricated by the bi-layer fabrication technique. Using these membranes, we investigated the effect of changing the pressure of the annealing gas (H 2) on annealing time at temperatures between 450 °C and 550 °C. X-ray diffraction (XRD) was used to stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
9
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(11 citation statements)
references
References 43 publications
2
9
0
Order By: Relevance
“…Comparing the data in Figure with the standard PDF card, the diffraction peaks at 30.21°, 35.04°, 43.04°, 53.41°, 57.02°, and 62.54° correspond to the inverse spinel Fe 3 O 4 face‐centered cubic lattice (220), (311), (400), (422), (511), (440) crystal planes . The diffraction peaks at 2θ = 40.10° correspond to the (111) crystal planes of Pd nanoparticles . The XRD characterization results showed that the cubic spinel‐structured Fe 3 O 4 nanocrystal was obtained and Pd 2+ was reduced to Pd.…”
Section: Resultsmentioning
confidence: 92%
“…Comparing the data in Figure with the standard PDF card, the diffraction peaks at 30.21°, 35.04°, 43.04°, 53.41°, 57.02°, and 62.54° correspond to the inverse spinel Fe 3 O 4 face‐centered cubic lattice (220), (311), (400), (422), (511), (440) crystal planes . The diffraction peaks at 2θ = 40.10° correspond to the (111) crystal planes of Pd nanoparticles . The XRD characterization results showed that the cubic spinel‐structured Fe 3 O 4 nanocrystal was obtained and Pd 2+ was reduced to Pd.…”
Section: Resultsmentioning
confidence: 92%
“…Through contrasting the data in Figure with the standard PDF card, the diffraction peaks at 30.11°, 35.44°, 43.14°, 53.41°, 57.02°, and 62.54° correspond to (220), (311), (400), (422), (511), (440) crystal planes of the inverse spinel face‐centered cubic Fe 3 O 4 (JCPDS 85–1436) . From Figure (b), the diffraction peaks at 39.81° and 46.36° correspond to (111) and (200) crystal planes of Pd nanoparticles (JCPDS 46–1043) . On the basis of the results, Pd 2+ is reduced to Pd, and Fe 3 O 4 /P (GMA‐DVB)‐PEI/Pd microspheres catalyst is produced.…”
Section: Resultsmentioning
confidence: 99%
“…This drawback can be avoided by working at operating conditions above the mentioned critical point when membrane is exposed to hydrogen or modifying the Pd phase diagram [ 189 ]. The last option can be realized by alloying pure Pd with other metals, i.e., silver [ 52 , 106 , 190 , 191 , 192 ], copper [ 99 , 102 ], ruthenium [ 187 , 193 ] or gold [ 194 , 195 ]. It is demonstrated that Pd-based alloys with specific concentrations of these metals modify the metal-hydride phase diagram avoiding the mentioned embrittlement phenomena [ 28 ].…”
Section: Pd-alloy Membranesmentioning
confidence: 99%
“…However, recent developments prefer faster processes in pressurized hydrogen atmosphere. In this case, it is proposed that dissolved hydrogen forms vacancies in the crystal lattice of palladium favouring the mobility of other alloy constituents and, consequently, reducing the time required to obtain the alloy [ 195 ]. As previously mentioned, layers prepared by co-deposition need softer thermal treatments (shorter times or lower temperatures) for annealing as compared with layers generated by sequential deposition (either consecutive or alternative) [ 95 , 202 ].…”
Section: Pd-alloy Membranesmentioning
confidence: 99%